Leveling the field for biofuels: Comparing the economic and environmental impacts of biofuel and other export crops in Malawi - Schuenemann, Franziska; Thurlow, James; Zeller, Manfred (Wiley, 2017)
Biofuels often raise the specter of food insecurity, water resource depletion, and greenhouse gas emissions from land clearing. These concerns underpin the “sustainability criteria” governing access to European biofuel markets. However, it is unclear if producing biofuels in low‐income countries does exacerbate poverty and food insecurity, and moreover, whether the sustainability criteria should apply to all agricultural exports entering European markets. We develop an integrated modeling framework to simultaneously assess the economic and environmental impacts of producing biofuels in Malawi. We incorporate the effects of land use change on crop water use, and the opportunity costs of using scarce resources for biofuels instead of other crops. We find that biofuel production reduces poverty and food insecurity by raising household incomes. Irrigated outgrower schemes, rather than estate farms, lead to better economic outcomes, fewer emissions, and similar water requirements. Nevertheless, to gain access to European markets, Malawi would need to reduce emissions from ethanol plants. We find that biofuels’ economic and emissions outcomes are generally preferable to tobacco or soybeans. We conclude that the sustainability criteria encourage more sustainable biofuel production in countries like Malawi, but are perhaps overly biased against biofuels since other export crops raise similar concerns about food security and environmental impacts.